KEY PRINCIPLES OF TECHNOLOGY TRANSFER OF A SLAM-ORIENTED UAV PLATFORM FOR LIDAR MONITORING IN AGRICULTURAL SYSTEMS AND RADIATION CONTAMINATION ZONES - Семіряков, Олександр (SWorldJournal, 2026)
The article is devoted to the study of the possibilities of transferring SLAM-oriented platform technologies using LIDAR monitoring to the agricultural sector and the sphere of limited physical access associated with radiation. The purpose of the article